Child Marriage and Its Impacts on the Education of Girls in the Rural Gambia: Focus on Niani District - Barrow, Abdou; Bah, Yahya Muhammed; Sanneh, Mbassi (UIII Press, 2022)
Twenty-one percent of young women married before the age of eighteen. Approximately 650 million girls and women are married before their 18th birthday (UNICEF, 2020, 2021). States member of the United Nations, through its Sustainable Development Goals, has committed to ending child marriage globally through laws, legislation, and other means. Though the practice of child marriage is declining globally, it remains prevalent in Africa and Asia, particularly in the Gambia. This study looks at the impact of child marriage on girls' education in rural Gambia and the factors that encourage it. The researchers conducted qualitative case study research through documentation, Focus Group discussion (FGD), observation, and interviews to collect data. The study's findings indicate that child marriage has negative impacts on girls' education in rural Gambia. This reveals the fact that the percentage of girls enrolled in schools, especially high school, is lower than boys. Girls also face more difficulties than boys to complete, retain and transit to secondary or higher education. This leaves them with no future and excludes them from social or economic advantages. The factors that encourage child marriage are included: religion, poverty, culture, lack of meaningful opportunity, older men's desire for younger women to marry, and the failure of law enforcement. These factors mentioned repeatedly perpetuate the practice of child marriage, and undermine the educational opportunities for the majority of girls in the Niani district of Gambia. Therefore, the researchers recommend that the Gambian government enforce the existing laws and regulations to protect children’s fundamental rights and put into practice the necessary regulations on the prohibition and elimination of this phenomenon.